Combined treatment with dipeptidyl peptidase‐4 inhibitor (sitagliptin) and angiotensin‐II type 1 receptor blocker (losartan) suppresses progression in a non‐diabetic rat model of steatohepatitis. Issue 12 (13th February 2017) - Okura, Yasushi; Namisaki, Tadashi; Moriya, Kei; Kitade, Mitsuteru; Takeda, Kosuke; Kaji, Kosuke; Noguchi, Ryuichi; Nishimura, Norihisa; Seki, Kenichiro; Kawaratani, Hideto; Takaya, Hiroaki; Sato, Shinya; et al.
Abstract : Aim: Dipeptidyl peptidase‐4 (DPP4) inhibitors (DPP4‐I) are oral glucose‐lowering drugs for type 2 diabetes mellitus. Previously, we reported that DPP4‐I (sitagliptin) exerted suppressive effects on experimental liver fibrosis in rats. Blockade of the renin–angiotensin system by angiotensin‐II type 1 receptor blocker (losartan), commonly used in the management of hypertension, has been shown to significantly alleviate hepatic fibrogenesis and carcinogenesis. We aimed to elucidate the effects and possible mechanisms of a sitagliptin + losartan combination on the progression of non‐diabetic non‐alcoholic steatohepatitis (NASH) in a rat model. Methods: To induce NASH, Fischer 344 rats were fed a choline‐deficient L‐amino acid‐defined diet for 12 weeks. We elucidated the chemopreventive effects of sitagliptin + losartan, especially in conjunction with hepatic stellate cell (HSC) activation, angiogenesis, and oxidative stress, all known to play important roles in the progression of NASH. Results: Sitagliptin + losartan suppressed choline‐deficient L‐amino acid‐defined diet‐induced hepatic fibrogenesis and carcinogenesis. The combination treatment exerted a greater inhibitory effect than monotherapy. These inhibitory effects occurred almost concurrently with the suppression of HSC activation, neovascularization, and oxidative stress. In vitro studies showed that sitagliptin + losartan inhibited angiotensin II‐induced proliferation and expression of transforming growth factor‐β1 and α1 (I)‐procollagen mRNA of activated HSC and in vitro angiogenesis, in parallel with the suppression observed in in vivo studies. Conclusions: The widely and safely used sitagliptin + losartan combination treatment in clinical practice could be an effective strategy against NASH.